Balancing internal capabilities and external funding: A study on the financial sustainability of people’s credit funds in Vietnam - Phan, Huy Duong; Le, Ngoc Thang; Nguyen, Bao Huyen; Tran, Thanh Long; Nguyen, Le Thao Huong (Edelweiss Applied Science and Technology, 2025)
This study examines the determinants of financial sustainability in Vietnam’s People’s Credit Funds (PCFs) using a quantitative model. The results indicate that customer outreach has the most significant positive effect, followed by loan portfolio management, organizational capacity, productivity, governance quality, and transparency. These findings emphasize the importance of expanding client access, improving internal efficiency, and strengthening governance structures to enhance sustainability. In contrast, financial autonomy exhibits a negative impact, suggesting that PCFs may not yet be ready for full independence without gradual institutional support. Financial management, while positively associated, does not show statistical significance. The study enriches microfinance literature by offering a comprehensive framework that captures both internal and external drivers of sustainability. It also provides practical guidance for PCF managers and policymakers to improve operational performance and carefully plan the transition toward greater financial independence based on institutional capacity.